A Comparison of "le" in Mandarin Chinese and "lɛɛw" in Thai - Amporndanai, Suchathip (Journal of Sinology (วารสารจีนวิทยา), 2007)
The purpose of this study is to compare the grammatical meaning and syntactic structure of "le1" and "le2" in Mandarin Chinese, and those of "le" in Mandarin Chinese and "lɛɛw" in Thai. The study shows that "le1" is an aspect marker indicating either completion of action or change, depending on the types of co-occurring indicates the occurrences of a new situation or a new state. Comparing "le1" and "le2" in Mandarin Chinese with "lɛɛw" in Thai, we find that "lɛɛw" in Thai shares similar grammatical meanings with "le1" and "le2" in Mandarin Chinese.